Combination of thidiazuron and basal media type on optimizing in vitro growth of Grammatophyllum stapeliiflorum orchids - Yuniati; Isda, Mayta Novaliza (Jurnal Ilmiah Pertanian, 2024)
Grammatophyllum stapeliiflorum, recognized as the melancholic orchid, represents one of the elusive orchid species facing the brink of extinction, thus exacerbating its rarity. Tissue culture technology becomes imperative for the propagation of this orchid species. This study aims to scrutinize the influence of different concentrations of the synthetic growth regulator thidiazuron (TDZ) on distinct basal media types, Murashige Skoog (MS) and Vacin and Went (VW), on the in vitro growth of G. stapeliiflorum orchids. Employing a complete randomized factorial design, the study entails two research factors: TDZ concentration with 4 treatment levels, A0 = 0 mg/L, A1 = 0.25 mg/L, A2 = 0.50 mg/L, and A3 = 0.75 mg/L, and the second factor being the media type, B1 = ½ MS and B2 = ½ VW. Findings indicate significant effects of MS and VW media on the percentage of viable explants, browning, globular forms, and shoots. Interaction between TDZ concentration and media type didn't yield significant effects on each experimental parameter. Treatment with 0.25 and 0.50 mg/L TDZ on ½ VW media demonstrated optimal results for explant growth percentage, browning, and explants in the globular phase, at 97.33%, 2.67%, and 2.67%, respectively. Moreover, treatment with 0.75 mg/L TDZ on ½ VW media resulted in the highest percentage of explant coloration. The combination of TDZ and media has shown the potential to enhance the production efficiency and conservation of this rare orchid species through tissue culture technology.